Implementation of Qawa'id Al-Fiqhiyyah Mazhab Hambali in Islamic Economic - Hendrianto Hendrianto; Hasan Bisri (AL-FALAH : Journal of Islamic Economics, 2021)
Purpose: This research aims to provide knowledge about qawa'id al-fiqhiyyah Hambali sect thought and its application in sharia economic law seen of the four popular rules of jurisprudenceDesign/Method/Approach: This research is library research, using documentation data collection techniques, and data analysis using content analysisFindings: Results showed that qawaid fiqiyyah dissect Hambali's for bidden right speed before the time, over the main push of the lift, badal (substitute) is positioned mubdal (replaced), and the latter considered common practice, while rare, and there is no law to him. The fourth method is able to address the problem Kulli (general), and in particular the problems of legal jurisprudence of Islam among the modern economy, which in this case study can not be separated from AL Quran and Hadits.Originality/Values: The main contribution of this research is to fill the gap in how the implementation of qawa'id al-fiqhiyyah mazhab hambali in Islamic economic law.